2010
DOI: 10.1680/stbu.2009.163.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of drystone retaining structures

Abstract: Drystone walling is an ancient form of wall construction, used worldwide wherever there is an abundance of raw building materials. However, very little research has been conducted on these structures, making their analysis difficult. As part of an ongoing investigation, four full-scale drystone retaining walls were built and tested to failure in a bespoke outdoor test laboratory. Through the course of the testing, the distinctive bulge patterns that are found in many in situ walls were successfully recreated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…There is now a renewed interest in dry stone masonry. As many walls build in the 19th and at the beginning of the 20th century are aging, modern engineering tools are needed to assess their mechanical performances [91,92]. The environmental impact of natural stones and aggregates is extensively discussed by Calkins [84].…”
Section: Concretementioning
confidence: 99%
“…There is now a renewed interest in dry stone masonry. As many walls build in the 19th and at the beginning of the 20th century are aging, modern engineering tools are needed to assess their mechanical performances [91,92]. The environmental impact of natural stones and aggregates is extensively discussed by Calkins [84].…”
Section: Concretementioning
confidence: 99%
“…Simulations on drystone constructions fall into two categories: (a) macro-mechanical approaches, where the masonry is treated as a continuous medium (Arya & Gupta, 1983;Cooper, 1986;Villemus et al, 2007;Mundell et al, 2009); and (b) micro-mechanical approaches (finite-or distinct-element methods), where the wall is represented as a combination of blocks (Dickens & Walker, 1996;Harkness et al, 2000;Powrie et al, 2002;Zhang et al, 2004;Claxton et al, 2005). In addition, only a few recent experiments have been undertaken on drystone retaining structures (Villemus et al, 2007;Mundell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, experimental studies are usually rare because difficult to undertake : in the literature can be found laboratory tests on periodic masonry [9] as well as recent on-site experiments on dry-stone retaining walls [10,11,12].…”
Section: Introductionmentioning
confidence: 99%